Empathic Approach in Classroom Activities to Support Gender-Responsive Education at the Sixth-Grade Elementary Students - Vera Sardila; R. Hariyani Susanti; Muhammad Ilham Syarif; Aramudin (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2023)
This paper examines the role of empathy in fostering a gender-sensitive atmosphere in elementary schools, especially among sixth-grade students. It seeks to address the issue of lack of empathy, which has been linked to the prevalence of sexism, misogyny, and sexual abuse in today’s society. The research objective is to assess the efficiency of incorporating an empathetic approach in classroom activities to enhance gender awareness among students. The research uses a qualitative experimental design and an empathetic approach by applying Gender Responsive Scorecard (GRS) and Empathy map as the foundation of activities design. The research result indicates and provides evidence of the effectiveness of the empathic approach in improving students' understanding of experiences that differ from their own, especially regarding gender. In addition, the results will guide educators and researchers on how to incorporate an empathetic approach in promoting gender responsiveness in the classroom.